Political connections and the cost of equity capital - Boubakri, Narjess (2012)
Motivated by recent research on the costs and benefits of political connection, we examine the cost of equity capital of politically connected firms. Using propensity score matching models, we find that politically connected firms enjoy a lower cost of equity capital than their non-connected peers. We find further that political connections are more valuable for firms with stronger ties to political power. In additional analyses, we find that the effect of political connection on firms' equity financing costs is influenced by the prevailing country-level institutional and political environment, and by firm characteristics. Taken together, our findings provide strong evidence that investors require a lower cost of capital for politically connected firms, which suggests that politically connected firms are generally considered less risky than non-connected firms.